2020
DOI: 10.1108/md-01-2018-0104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inter- and intra-regional geographic diversification strategies on firm performance in China

Abstract: Purpose The purpose of this paper is to theorize and empirically examine the effects of intra- and inter-regional geographic diversification on firm performance in China. Furthermore, it investigates they key firm capabilities, which moderate the relationships between intra- and inter-regional geographic diversification and firm performance. Design/methodology/approach In this research, the authors studied 366 listed companies that invest in mainland China. The authors used the Taiwan Economy Journal databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…The results of this test are in line with the results of research conducted by several previous studies which found a significant positive effect [49,16,14] and [17]. Several previous studies that are not in harmony with the results of this study are [19]. The test results which show a significant positive effect prove that hypothesis 1 is proven.…”
Section: A Validity Test Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this test are in line with the results of research conducted by several previous studies which found a significant positive effect [49,16,14] and [17]. Several previous studies that are not in harmony with the results of this study are [19]. The test results which show a significant positive effect prove that hypothesis 1 is proven.…”
Section: A Validity Test Resultssupporting
confidence: 90%
“…Previous studies have used the managerial ability variable on financial performance and found a significant positive effect [15,16,14,17]; and [18]. Another study found that there was an insignificant effect on managerial ability on financial performance [19]. H1 = Managerial capability has a significant positive effect on financial performance…”
Section: A Effect Of Managerial Ability On Financial Performancementioning
confidence: 95%
“…Enterprises’ investment in China is of great research importance (Li et al , 2019; Tsai et al , 2020). Therefore, the research objective of this study is to assess investments in subsidiaries in China.…”
Section: Sample and Methodologymentioning
confidence: 99%
“…Based on China's environment, numerous scholars have paid attention to the relationships between diversification strategy and financial performance. However, owing to the different samples used by scholars, a consistent conclusion still remains to be found [9][10][11]19,20].…”
Section: Diversification Strategy and Financial Performancementioning
confidence: 96%
“…Numerous foreign enterprise groups entered the Chinese market, resulting in many successful cases of diversification. Although Chinese enterprises have been implementing diversification strategies for over 40 years, they remain at the exploratory stage in general [9]. With the emergence of cases of failed diversification, such as Lenovo, Giant, LeTV, and other large enterprise groups, numerous cases of the improper selection of diversification strategy types and the incorrect symmetry of organizational structure and diversification strategy have occurred.…”
Section: Introductionmentioning
confidence: 99%